An Anthology for Young Writers - Meredith, Robert C. (Lincolnwood National Textbook Company, 1986)
Shows the writer different articles in order that they can teach themselves how to effectively write, based on how someone else has written an article. You must teach yourself the technique behind the article so that you can then write on your own.
Keywords: Fiction